(untitled) (Eurasian Journal of Research, Development and Innovation, 2023)
Achieving optimal adhesion between polymers and aluminum is paramount for diverse engineering applications, and several techniques have been explored to realize this. This review elucidates the various methodologies employed, dividing them into dry and wet processing techniques. Dry processing emphasizes controlled surface modifications but can be capital-intensive, while wet processing, though economically viable, sometimes requires potentially hazardous chemicals. Central to both techniques is the goal of augmenting the aluminum’s bonding surface by inducing micro-level roughness. Moreover, polymers with inherent carbonyl groups have shown promising spontaneous adhesion to the alumina layer of aluminum, offering a robust interface without the necessity for exhaustive surface treatments. While such treatments can bolster interface strength, their indispensability varies based on the specific polymer-aluminum pairing. Decisions regarding surface treatment methodologies should be judiciously made, considering the specific application and polymer in use. give me a sutable keywords